1986
DOI: 10.2307/1221904
|View full text |Cite
|
Sign up to set email alerts
|

CONCEPTS OF RARITY IN VASCULAR PLANT SPECIES, WITH SPECIAL REFERENCE TO THE GENUS CALOCHORTUS PURSH (LILIACEAE)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. International Association for Plant Taxonomy (IAPT)is collaborating with JSTOR to digitize, preserve and extend access to Taxon. SummaryThe concept of rarity in vascular plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 77 publications
(73 reference statements)
0
45
0
3
Order By: Relevance
“…Rarity can have many causes, which include terrestrial history, the history of previous land-use, the age of the taxa, the ecology of the species, evolutionary history, population dynamics, reproductive biology, as well as stochastic events (Kubitzki 1976;Fiedler 1986;Fiedler and Ahouse 1992). Additionally, problems related to taxonomic identiWcation or inappropriate sampling techniques may lead to apparent rarity or abundance (Gaston 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Rarity can have many causes, which include terrestrial history, the history of previous land-use, the age of the taxa, the ecology of the species, evolutionary history, population dynamics, reproductive biology, as well as stochastic events (Kubitzki 1976;Fiedler 1986;Fiedler and Ahouse 1992). Additionally, problems related to taxonomic identiWcation or inappropriate sampling techniques may lead to apparent rarity or abundance (Gaston 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Two patterns are possible: older taxa might have more threatened species if extinction probability increases through time, or fewer threatened species if greater taxon age reflects better survival abilities (Stanley, 1979;Fiedler, 1986;Smith, 1994). The former pattern is the more likely, because all species must *Address all correspondence to Kevin J.…”
Section: Introductionmentioning
confidence: 99%
“…Although this does not follow the general trend for plants, there are a number of studies that have also shown no association between geographic distribution and levels of genetic diversity (Gitzendanner and Soltis 2000). This example emphasises a number of general issues raised by various authors in relation to the causes of rarity and restricted geographical distribution (Fiedler 1986;Fiedler and Ahouse 1992;Kunin and Gaston 1993). Rarity has multiple origins and therefore the genetic consequences of rarity cannot be generalized in a simplistic fashion.…”
Section: Discussionmentioning
confidence: 82%